Impact on the level of self-confidence, satisfaction and perception of clinical simulation in medical students at a private university - Vargas-Rubio, Víctor Alonso (2024)
Background: Learning through clinical simulation allows the development of technical and non-technical skills demonstrated in both undergraduate and graduate degrees. The level of self - confidence and satisfaction of the students, as well as, the good perception on the part of these is important and is relatedto the repetition of simulation sessions. Objective: In order to evaluate the impact of simulation on the level of confidence, satisfaction and perception in undergraduate students at a private university. Material and methods: A descriptive cross-sectional study was carried out. The sixth- year medicalstudents who were carrying out their high-fidelity simulation practices were invited to participate; they were administered the “Questionnaire on the level of confidence and satisfaction in hospital clinical simulation practices” and the exploratory questionnaire “Perception of hospital clinical simulation practices” online. Results: From a total of 59 students, the results of the “Questionnaire level of self- confidence and satisfaction in hospital clinical simulation practices” were obtained, which presented an average satisfaction of 4.64 ± 0.08 and in the dimension of confidence an average of 4.57 ± 0.15. From the perception survey, more than half of the students considered that the simulation improved their skills and abilities for clinical practice. Conclusion: Clinical simulation has a good impact on the level of self-confidence, satisfaction and perception in undergraduate students of a private university.